Intracranial Hemorrhage in a Patient of Hemophilia A with Factor VIII Inhibitors Positive: A Case Report - Ninan, Melvin K.; Chennupati, Prabhu K.; Gurrala, Shekhar R. (Journal of Neuroanaesthesiology and Critical Care, 2025)
Management of intracranial hemorrhage in a patient with hemophilia A and high-titer inhibitors presents a significant challenge to the neurointensivist. The decision between conservative and surgical approaches involves a delicate risk–benefit balance. While conservative management is costly and carries the risk of sudden deterioration, surgical intervention is often complicated by the high likelihood of rebleeding. We report the successful critical care management of a 50-year-old male with hemophilia A and high-titer factor VIII inhibitors who presented with an acute-on-chronic subdural hematoma. His factor VIII levels were markedly low, and conventional factor VIII replacement therapy was ineffective. The bleeding manifestations and laboratory parameters did not improve with standard treatment. The patient was successfully managed using sequential or combined bypassing agent therapy.
Keywords: hemophilia A; ICH; antihemophilic factors; sequential/combined bypass agent therapy